2000
DOI: 10.1007/s002130000419
|View full text |Cite
|
Sign up to set email alerts
|

Is benzodiazepine-induced amnesia due to deactivation of the left prefrontal cortex?

Abstract: These results suggest that a specific interaction with prefrontal cortex activation does not underlie the amnesic effect of midazolam. However, it remains possible that a threshold level of prefrontal rCBF is necessary for encoding and that, after midazolam, this was not reached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…Thus, given the known role of the BG/DA system in reinforcement learning, and the converging results with Parkinson's disease patients (Frank et al, 2004), together with the arguments for preferential drug action in striatum described above, it should be relatively uncontroversial that the learning effects reported here stemmed from DA effects within the BG and these effects would be more difficult to explain with prefrontal mechanisms. This is further supported by our recent findings with the drug midazolam, which inactivates the PFC (and hippocampus) but leaves the striatum unaffected (e.g., Bagary et al, 2000;Reinsel et al, 2000). We found that whereas this drug profoundly impaired explicit memory processes, it spared probabilistic reinforcement learning (both positive and negative) and even enhanced some implicit forms of this learning (Frank, O'Reilly, & Curran, in press).…”
Section: Dopamine Effects In Prefrontal Cortex: D 1 and D 2 Receptorssupporting
confidence: 88%
“…Thus, given the known role of the BG/DA system in reinforcement learning, and the converging results with Parkinson's disease patients (Frank et al, 2004), together with the arguments for preferential drug action in striatum described above, it should be relatively uncontroversial that the learning effects reported here stemmed from DA effects within the BG and these effects would be more difficult to explain with prefrontal mechanisms. This is further supported by our recent findings with the drug midazolam, which inactivates the PFC (and hippocampus) but leaves the striatum unaffected (e.g., Bagary et al, 2000;Reinsel et al, 2000). We found that whereas this drug profoundly impaired explicit memory processes, it spared probabilistic reinforcement learning (both positive and negative) and even enhanced some implicit forms of this learning (Frank, O'Reilly, & Curran, in press).…”
Section: Dopamine Effects In Prefrontal Cortex: D 1 and D 2 Receptorssupporting
confidence: 88%
“…Specifically, these competitive dynamics serve to sharpen cognitive representations by amplifying activity in the most active, task-relevant, representations (e.g., the most appropriate word to complete a sentence) and suppressing competing representations (e.g., for the many other word possibilities). A tenet of the model is that these critical dynamics occur via inhibitory, GABAergic interneurons (12)(13)(14). Here we test the predictions of the model regarding selection processes that are supported by the left ventrolateral prefrontal cortex.…”
mentioning
confidence: 94%
“…The results revealed significant deactivation in the midazolam condition during episodic memory encoding in the calcarine sulci bilaterally (BA 17), but not in the prefrontal cortex. An account of the differences between the Coull et al (1999) and Bagary et al (2000) studies in regions showing benzodiazepineinduced deactivation during encoding is not readily apparent, but may be related to methodological differences between the studies, such as the modality of stimulus presentation (i.e., visual vs. auditory) and the nature of the control task to which the encoding task was compared.…”
Section: It Is Well Documented That Acute Administration Of the Benzomentioning
confidence: 99%
“…Although the generalizability of these results to other measures of executive function may be questioned, this study provides strong evidence that different effects of benzodiazepines can be dissociated using PET. Bagary et al (2000) recently reported results of a placebo-controlled 746 M.Z. Mintzer et al N EUROPSYCHOPHARMACOLOGY 2001 -VOL .…”
Section: It Is Well Documented That Acute Administration Of the Benzomentioning
confidence: 99%
See 1 more Smart Citation